2015
DOI: 10.1007/s00402-015-2309-4
|View full text |Cite
|
Sign up to set email alerts
|

Meniscal tears associated with anterior cruciate ligament injury

Abstract: The incidence of meniscal tear associated with ACL injury is higher in chronic cases; the number of medial meniscal tears is particularly high, many of which require meniscectomy. Early ACL reconstruction is recommended also for the prevention of secondary meniscal tear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
116
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(133 citation statements)
references
References 13 publications
13
116
2
2
Order By: Relevance
“…Moreover, the use of tendon or ligament offers the advantage of isolating cells from a site other than an injured meniscus, which may improve patient outcomes. In ACL injuries, associated menisci tears are seen in approximately half of the cases 22,23 . As a consequence, in these cases, the remnants of the torn ACL can be harvested for cells which can then be combined in co-culture with articular chondrocytes towards engineering a new autologous knee meniscus.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the use of tendon or ligament offers the advantage of isolating cells from a site other than an injured meniscus, which may improve patient outcomes. In ACL injuries, associated menisci tears are seen in approximately half of the cases 22,23 . As a consequence, in these cases, the remnants of the torn ACL can be harvested for cells which can then be combined in co-culture with articular chondrocytes towards engineering a new autologous knee meniscus.…”
Section: Discussionmentioning
confidence: 99%
“…The association of meniscal tears with ligamentous injuries has been most extensively studied in the setting of ACL tears. A recent study demonstrated meniscal tears in 72% of patients with acute ACL tears and 85% with chronic ACL tears (26). In acute ACL tears, the lateral meniscus alone was involved in 70%, the medial meniscus alone was involved in 10%, and both menisci were involved in 20%.…”
Section: State Of the Art: Athletic Injuries Of Knee Ligaments And Mementioning
confidence: 98%
“…In acute ACL tears, the lateral meniscus alone was involved in 70%, the medial meniscus alone was involved in 10%, and both menisci were involved in 20%. In contrast, in chronic ACL tears, the lateral meniscus alone was involved in 34%, the medial meniscus alone was involved in 25%, and both menisci were involved in 41% (26). Ninety percent of peripheral vertical longitudinal meniscal tears are seen in patients with ACL tears, and the presence of a peripheral vertical meniscal tear should raise suspicion for an associated ACL tear (27) (Fig 3).…”
Section: State Of the Art: Athletic Injuries Of Knee Ligaments And Mementioning
confidence: 99%
“…The offset in external rotation of the femur after ACL transection causes changes in the contact point on the tibia which may attribute to the increase in the number of knees with common profiles in the central portion of the medial meniscus, the increased profile area from Profile 3 to 3′ and the identification of the new profile on the lateral plateau. Moreover, such changes in contact stress profiles in areas covered by the meniscus correspond to the increased incidence of medial meniscus damage in chronic ACL deficient knees (Bellabarba et al, 1997; Hagino et al, 2015). The altered rotational mechanics can lead to significant cartilage loss in the posterior medial tibial plateau, observed in Andriacchi et al (2006), and offloading of areas that were highly loaded (Andriacchi et al, 2006; Andriacchi and Mundermann, 2006; Chaudhari et al, 2008) – as was observed with fewer knees identifying with Profile 2 to 2′ after ACL transection.…”
Section: Discussionmentioning
confidence: 99%